The Effectiveness of Health Education about Gout Arthritis Diet Compliance and Uric Acid Levels in Gout Arthritis Patients - Cyntia Theresia Lumintang; Syenshie Virginia Wetik (STIKES Ngesti Waluyo, 2022)
The habit of consuming seafood and also some lifestyle in Minahasa culture contributes to the increase cases of gout arthritis. This is also supported by the lack of knowledge and information about the correct diet for gouty arthritis sufferers. The existence of the right information can help sufferers to implement a healthy diet so that it can reduce uric acid levels. The purpose of this study was to assess the effectiveness of health education on uric acid levels in gouty arthritis sufferers. This study was conducted with a quasi-experimental research design, using one group pretest-posttest approach on 30 gout arthritis patients in Bongkudai Selatan Village, North Sulawesi. The sampling technique used was accidental sampling, and the data were analyzed using univariate and bivariate analysis. The results showed that there was a decrease in uric acid levels in 70% of respondents and there was an effect of health education on uric acid levels with a p value of 0.0325.